Métodos de extração e determinação do herbicida glifosato: breve revisão - Amarante Júnior, Ozelito Possidônio de; Santos, Teresa Cristina Rodrigues dos; Brito, Natilene Mesquita [UNESP]; Ribeiro, Maria Lúcia [UNESP] (Sociedade Brasileira de Química, 2002)
This paper supplies a compact revision about the main extraction, clean-up and pre-concentration methods of the herbicide glyphosate for water and soil samples, as well as methods for its determination and quantification.
Methods of extraction and determination of the herbicide glyphosate: compact revision
Keywords: glyphosate; extraction; determination